2014
DOI: 10.1016/j.tranon.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Oral Premalignant and Malignant Lesions Using Fluorescently Labeled Lectins

Abstract: Aberrant glycosylation during carcinogenesis results in altered glycan expression on oral cancer cells. The objective of this study was to detect this atypical glycosylation via imaging of fluorophore-conjugated lectins. Paired normal and tumor tissue from seven patients with oral squamous cell carcinoma were investigated for sialic acid expression via the legume protein wheat germ agglutinin (WGA). Fluorophore (Alexa Fluor 350 and Alexa Fluor 647) conjugated WGA was topically applied to the tissue samples and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…1,6 A new method based on the change in expression of certain glycan residues on the surface of cancerous and dysplastic cells shows promising initial results. 16,17 A chairside in vivo study by Baeten et al tested a specific fluorescent conjugated lectin to target this aberrant glycosylation on cancerous and dysplastic cells in the oral cavity. The study yielded a sensitivity of 89% and a specificity of 82% in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 A new method based on the change in expression of certain glycan residues on the surface of cancerous and dysplastic cells shows promising initial results. 16,17 A chairside in vivo study by Baeten et al tested a specific fluorescent conjugated lectin to target this aberrant glycosylation on cancerous and dysplastic cells in the oral cavity. The study yielded a sensitivity of 89% and a specificity of 82% in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have shown that sialic acid levels can distinguish between normal subjects and subjects with OPMDs and cancerous lesions . Additionally, we previously showed the ability of WGA‐FITC to differentially stain malignant biopsies compared with normal biopsies . However, the ability of WGA‐FITC to differentially stain malignant tissue in vivo in a clinically relevant timeframe (ie, seconds compared to 30‐60 minutes in previous testing) is profound as WGA‐FITC is a semi‐large protein (36 kDa) and requires time to diffuse and bind sialic acid.…”
Section: Discussionmentioning
confidence: 79%
“…10,12,24 Additionally, we previously showed the ability of WGA-FITC to differentially stain malignant biopsies compared with normal biopsies. 6 However, the ability of WGA-FITC to differentially stain malignant tissue in vivo in a clinically relevant timeframe (ie, seconds compared to 30-60 minutes in previous testing) is profound as WGA-FITC is a semi-large protein (36 kDa) and requires time to diffuse and bind sialic acid. The data presented in this article agrees well with prior research as WGA-FITC LOD scores directly correlate with greater malignancy progression regardless of the cancer type (LOD scores: cancerous lesions > dysplastic lesions > benign lesions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycosylation is also expected to be used in the early diagnosis of HNC. Inspired by the aberrant glycan expression in oral cancer tissues, a study (42) applied legume protein wheat germ agglutinin (WGA) to selectively recognize sialic acid and N-acetylglucosamine residues, and detected atypical glycosylation via imaging of fluorophore-conjugated lectins. The results demonstrated that WGA fluorophore probes can successfully yielding statistically higher fluorescence in OSCC tissues, which exhibited its promising ability to distinguish cancerous tissues from pathologically normal tissues.…”
Section: Glycosylationmentioning
confidence: 99%